Persuasive Organizational Patterns and Rhetorical Arguments in Donald Trump’s Policy Speech on Jerusalem - Salman Hummadi, Ali; Binti M. Said, Seriaznita; Bin A. Manan, Amerrudin (International Journal of Psychosocial Rehabilitation, 2019)
he skill of human communication is so crucial in the sense that the most successful and powerful people over the centuries are those who have mastered the ability of persuasive public speaking. Persuasion is the art of persuading people to form preferable social beliefs towards certain issues such as Jerusalem, and, thus, acknowledged through the effective manipulation of various persuasive patterns and arguments. Based on Monroe’s (1955) motivated sequence pattern of organizing persuasive message, this article qualitatively analyses Trump’s policy speech on Jerusalem to identify its persuasive organizational patterns. The study further investigates Aristotle’ modes of argument(forensic, epideictic and deliberative) extending in the speech and their rhetorical functions in realizing those patterns. As an Arab, the researcher, being involved as a researcher participant rather than a passive reader at the research site, identifies the issue within the ambit of social beliefs. The results of the analysis demonstrated that Trump effectively and successfully employed organizational patterns to structure his persuasive discourse. Epideictic argument has been pervasively utilized by the speaker to realize attention, need and visualization steps of the motivated sequence pattern, while deliberative type is adopted to realize, partially, the satisfaction step, and, fully, the action step.